2015
DOI: 10.1159/000403245
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Platelet Concentrates with the Mirasol Pathogen Inactivation System Modulates Platelet Oxidative Stress and NF-κB Activation

Abstract: Background: Pathogen inactivation (PI) technologies for platelets aim to improve transfusion safety by preventing the replication of contaminating pathogens. However, as a consequence of treatment, aspects of the platelet storage lesion are amplified. Mirasol treatment also affects platelet signal transduction and apoptotic protein expression. The aim of this study was to examine the effect of Mirasol treatment on the generation of reactive oxygen species (ROS) and subsequent oxidative stress. Methods: Pooled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 51 publications
(66 reference statements)
5
26
0
2
Order By: Relevance
“…19,33 Previously, several studies have reported that RF and UV light can trigger intracellular generation of ROS in PLTs modulating signaling pathways and causing oxidative damage of macromolecules. 20,21,34 In this study, we also show that the RF/UV treatment generated intracellular H 2 O 2 in apheresis PCs throughout storage, which might contribute to the depolarization of the DW m further contributing to apoptosis development.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…19,33 Previously, several studies have reported that RF and UV light can trigger intracellular generation of ROS in PLTs modulating signaling pathways and causing oxidative damage of macromolecules. 20,21,34 In this study, we also show that the RF/UV treatment generated intracellular H 2 O 2 in apheresis PCs throughout storage, which might contribute to the depolarization of the DW m further contributing to apoptosis development.…”
Section: Discussionsupporting
confidence: 56%
“…Accumulating evidence demonstrates that PI-treated PLTs share highly similar behaviors with PLTs stimulated by physiologic activators, including PLT activation, degranulation, and development of apoptosis, leading to the conclusion that these processes have the same signaling mechanism. Lopez and coworkers 30 reported that thrombin induces translocation of Bax, Bak, and active Bid to MT resulting in cyto c release and subsequent loss 20,21,34 In this study, we also show that the RF/UV treatment generated intracellular H 2 O 2 in apheresis PCs throughout storage, which might contribute to the depolarization of the DW m further contributing to apoptosis development. …”
supporting
confidence: 68%
See 1 more Smart Citation
“…Supporting this notion, Johnson et al found higher levels of carbonylation in Mirasol ® -treated PCs compared to untreated buffy coat-derived PCs [20]. Carbonyl insertion into proteins occurs mainly by three mechanisms: amino acid backbone scission, amino acid side chain cleavage, and side chain ketone or aldehyde formation by metal catalysis [46].…”
Section: Alterations and Oxidation Of Platelet Proteinsmentioning
confidence: 99%
“…Der Riboflavinabbau ist zeitabhängig [98]. Umfangreiche toxikologische Untersuchungen sind unternommen worden, um die Sicherheit der mit MIRASOL® behandelten Blutprodukte nachzuweisen (Übersicht in [69,70] [17,115,116]. Dennoch finden sich nach einer PI mit MIRASOL® nur geringe Veränderungen am Gesamtproteom [67].…”
Section: Unerwünschte Effekte Der Pathogeninaktivierung Mit Mirasol®unclassified